2018
DOI: 10.1108/ils-08-2018-0091
|View full text |Cite
|
Sign up to set email alerts
|

Information literacy and learners’ satisfaction

Abstract: Purpose This paper aims to empirically examine the relationships among information literacy (IL), social networking technology usage (SNTU) and learners’ satisfaction (LS) among university students. The research also aims to determine whether SNTU has a mediating role in the relationship between IL and LS. Design/methodology/approach Based on the proposed framework, a self-administered questionnaire was adopted to gather data from students at Komar University of Science and Technology. Of a total of 520 ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This research also advanced the literature by exploring nine factors underlying green purchase behavior, namely, SI, QC, PH&EB, EC, CRS, PAGP, PC, PQI, and SO using EFA. The findings of the study are congruent with the previous studies suggesting that social influence (Asl & Khoddami, 2023; Khare & Kautish, 2021b), quality consciousness (Khare & Kautish, 2021a; Lago et al, 2020), perceived benefits (Mehta & Chahal, 2021), ecological concern (Chaudhary & Bisai, 2018; Jaiswal & Kant, 2018), consciousness toward resource‐saving (Joshi & Rahman, 2016; Kautish et al, 2019), perceived availability (Cerri et al, 2018; Sharma & Lal, 2020), price concerns (Niedermeier et al, 2021), perceived quality of information (Aljanabi & AL‐Hadban, 2023), and style orientation (Saleki et al, 2019) encourage green purchase behavior. The study's findings are valuable to marketers, scholars, and academicians in the field as they can obtain a better understanding of the various factors that affect green purchasing decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research also advanced the literature by exploring nine factors underlying green purchase behavior, namely, SI, QC, PH&EB, EC, CRS, PAGP, PC, PQI, and SO using EFA. The findings of the study are congruent with the previous studies suggesting that social influence (Asl & Khoddami, 2023; Khare & Kautish, 2021b), quality consciousness (Khare & Kautish, 2021a; Lago et al, 2020), perceived benefits (Mehta & Chahal, 2021), ecological concern (Chaudhary & Bisai, 2018; Jaiswal & Kant, 2018), consciousness toward resource‐saving (Joshi & Rahman, 2016; Kautish et al, 2019), perceived availability (Cerri et al, 2018; Sharma & Lal, 2020), price concerns (Niedermeier et al, 2021), perceived quality of information (Aljanabi & AL‐Hadban, 2023), and style orientation (Saleki et al, 2019) encourage green purchase behavior. The study's findings are valuable to marketers, scholars, and academicians in the field as they can obtain a better understanding of the various factors that affect green purchasing decisions.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant evidence that the perceived quality of information improves consumers' understanding of green products and influences their purchase behavior (Nekmahmud et al, 2022). Consumers tend to alter their consumption decisions if they view the information as trustworthy, logical, and dependable (Aljanabi & AL‐Hadban, 2023). The availability of accurate information assists consumers in recognizing eco‐friendly products and distinguishing them from those that are not, whereas insufficient information may impede consumers' ability to identify green products (Pickett‐Baker & Ozaki, 2008) and act as a barrier to the adoption of green purchase behavior (Testa et al, 2020).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…(2019) found that having an official Facebook group in a face-to-face academic course was associated with higher levels of course satisfaction through the mediating effect of social connectedness. Aljanabi and Al-Hadban (2018) found that students’ use of online social networks was associated with increased learner satisfaction from their studies. An additional study found that receiving peer feedback from collaborative blogging incorporated in a face-to-face course was associated with increased course satisfaction (Zhang et al ., 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individual Factors are more concentrated when it is second-order and conceptually is more reliable, besides second-order components reduce the number of paths in the model in which there is only one path from the Independent Variable to the Dependent Variable . To empirically test the model, the researcher applied a partial least square structural equation modeling (PLS-SEM) approach by SmartPLS (V. 3.2.8) (Aljanabi, 2017;Aljanabi et al, 2018Aljanabi et al, , 2019. Figure 1 shows the framework.…”
Section: Research Model and Hypothesismentioning
confidence: 99%